Tailoring the surface integrity and wear resistance of WE43 Mg alloy by warm laser shock peening - Bowen Li; Zongshen Wang; Meng Kong; Jin Li; Wenquan Wang; Tong Zang; Hongyu Zheng (Journal of Materials Research and Technology)
WE43 Mg alloy was processed by warm laser shock peening (WLSP) to tailor its surface integrity and wear resistance in this study. The influence rule of laser energy and process temperature as well as the tribological behavior of Mg alloy was revealed. The dimensions of impacted dents and surface roughness are raised with the increase of laser energy and temperature. A gradient microstructure is formed with the thickest grain refinement lay of 235 μm achieved by WLSP with 0.4 J at 150 °C. The highest surface hardness of 262.32 ± 67.32 HV is obtained with 0.4 J at room temperature (RT) with an increase of about 225% from the initial 80.82 ± 3.33 HV. All samples after WLSP exhibit enhanced wear resistance indicated by the reduced friction coefficient and even better tribological behavior examined at 200 °C than that at RT. The lowest average friction coefficient of 0.064 is achieved by WLSP with 0.4 J at RT and an acceptably low value of 0.126 is maintained with 0.4 J at 150 °C when worn at 200 °C. High-density dislocations and second-phase precipitation of Mg24Y5 and Mg41Nd5 are facilitated by dynamic strain aging (DSA) and dynamic precipitation (DP), leading to the improved grain refinement and surface modification results. The regular distribution of impacted dents, work hardening and grain refinement by surface severe plastic deformation as well as the promoted DSA and DP process during WLSP jointly contribute to the enhancement and thermal stability of the wear resistance of WE43 Mg alloy.